Adaptive capacity to climate change among the Chilika buffalo rearers of Odisha - BEHARA, SUBHRAJYOTI; GARAI, SANCHITA; MAITI, SANJIT; BHAKAT, MUKESH; MEENA, B S; BEHARA, JIBONJYOTI; DIXIT, A K; KADIAN, K S (The Indian Journal of Animal Sciences, 2022)
Climate change combined with human activities poses significant risks to people’s livelihood especially in developing countries. Adaptation at the community level is crucial in enabling them to respond to the direct and indirect effects of changes in climate. The present study was designed to assess the adaptive capacity of the Chilika buffalo rearers. So, the study was purposively conducted at the Chilika lake region of Odisha as it is the breeding tract of Chilika buffalo. A total 150 Chilika buffalo rearers were selected randomly from the cluster villages of the adjacent districts of Chilika lake. Sustainable Livelihood Approach (SLA) was used to develop Adaptive Capacity Assessment Index to measure the adaptive capacity of the Chilika buffalo rearers. They were having better physical capital (0.55) possession followed by social capital (0.48), financial capital (0.47), human capital (0.45) and natural capital (0.35). The average adaptive capacity of the Chilika buffalo rearers was found to be 0.46, which was quite unsatisfactory and majority of them (62.67%) were having a medium level of adaptive capacity to cope up with changing climatic scenario. Adaptive capacity of the Chilika buffalo rearers were having a strong and significant relationship with its every component. Therefore, to strengthen the adaptive capacity of the Chilka buffalo rearers, status of each and every capital has to be improved significantly.